Analysis and Optimization of High Temperature Thermochemical Energy Storage Systems for Concentrated Solar Power - Mathew, Arun (Curtin University, 2021)
This thesis presents a research investigation examining the thermal performance of thermochemical energy storage reactors suitable for applications in high temperature concentrated solar systems. An advanced numerical model was successfully developed for simulating the reactor packed bed thermal behaviour using both single-phase and (multi-phase) flow boiling mechanisms for heat exchange in the reactor. Two types of thermochemical storage media, namely magnesium hydride and calcium carbonate, were analysed for performance comparison providing different reaction kinetics.